2012
DOI: 10.1242/dev.075499
|View full text |Cite
|
Sign up to set email alerts
|

Clonal and molecular analysis of the prospective anterior neural boundary in the mouse embryo

Abstract: SUMMARYIn the mouse embryo the anterior ectoderm undergoes extensive growth and morphogenesis to form the forebrain and cephalic non-neural ectoderm. We traced descendants of single ectoderm cells to study cell fate choice and cell behaviour at late gastrulation. In addition, we provide a comprehensive spatiotemporal atlas of anterior gene expression at stages crucial for anterior ectoderm regionalisation and neural plate formation. Our results show that, at late gastrulation stage, expression patterns of ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 76 publications
2
62
0
Order By: Relevance
“…8D, Fig. S5) (Cajal et al, 2012). Dlx5 expression was confined to the proximal ectoderm in E7.5 control and N1ICD epi embryos (n=5/6; Fig.…”
Section: Notch Activation Induces Neural Specificationmentioning
confidence: 87%
See 2 more Smart Citations
“…8D, Fig. S5) (Cajal et al, 2012). Dlx5 expression was confined to the proximal ectoderm in E7.5 control and N1ICD epi embryos (n=5/6; Fig.…”
Section: Notch Activation Induces Neural Specificationmentioning
confidence: 87%
“…In order to investigate whether the NOTCH pathway can also play such an early role during in vivo neural development, we analysed the formation of neurectodermal tissue in N1ICD epi embryos. The transcription factor SOX1 is first expressed in the anterior region fated to become neurectoderm when the neural plate forms at E7.5 (Cajal et al, 2012;Pevny et al, 1998). Strikingly, we found that in N1ICD epi embryos Sox1 was expressed in an anterior distal domain at a time when Sox1 transcripts could not yet be detected in control littermates (n=10/11; Fig.…”
Section: Notch Activation Induces Neural Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed spatiotemporal expression analysis showed that AP2γ is expressed in the entire epiblast before HH stage 3 and gradually shifts outwards to the putative epidermal ectoderm at HH stage 4, accompanying with comple- mentary cSox2 expansion. Similarly, mouse AP2γ might have expression changes from ICM at E3.5 [47] to nonneural ectoderm at the late gastrulation stage [48]. The dynamic expression pattern of cAP2γ suggests that AP2γ might play multiple roles in ectodermal patterning in different regions of the epiblast.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse early embryo development, the neural fate commitment occurs during gastrulation, and a portion of anterior ectoderm is specified to adopt the neural fate (28,29). One of our previous studies documented the spatial transcriptome of the epiblast at the mid-gastrulation (E7.0) (29).…”
Section: Comparative Analysis Validates Module 3 Associated Day 8/10 mentioning
confidence: 99%